Peningkatan Partisipasi Usaha Kecil dan Mikro dalam Mencegah Penyebaran Covid-19 dan Pencapaian Target SDGs Nomor 3 di Kelurahan Tampan - Alfajri, Alfajri; Prakasa, Gading Bagus; Fernando, Fery; Vasnina, Afrah; Rahmatika, Aulia; Nazilah, Eliyatul; Habsi, Vanny Nur Delima (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2020)
The spread of the Covid-19 Pandemic has not shown any signs of a significant decline, both in Riau Province and in Pekanbaru City. Therefore, it takes various extra efforts carried out by multi-stakeholders, including higher education institution through its community service activity, to work in collaboration with the government to specifically impede the spread of Covid-19 and in general, achieve the Sustainable Development Goals (SDGs) number 3 (Good Health and Well Being). The method applied in this community service activity was counseling and dialogue to increase knowledge, awareness, and most importantly the participation of small and micro enterprises workers and owners as partners in this community service activity to prevent the spread of Covid-19. Before this community service activity, the level of discipline and compliance of the workers and the owners of the four partner restaurants was very low due to negligence reasons. After the implementation of the community service activity, there has been an increase in the participation of partners in carrying out the Covid-19 health protocol and achieving SDGs number 3 target. Key Words: Covid-19, Health Protocol, SDGs, Participation, Community Service.